EXPOSURE (SDL) IN PT. APLIKANUSA LINTASARTA - Fabian Robby; Drs. Sunarto Sunarto, SSi, MMSI (Jurnal Sistem Informasi, 1997)
With the existence of reporting systems that use this LKI database system, the treatment of mental status can be detected quickly. As a example if a customer wants to know until where the status of trouble handling of its data communications network, the customer service department can access the system and can alert to where the status handling.Â  For supervisors, the existence of this system can monitor the status of trouble handling so that if necessary further action can be decided more quickly.